2022
DOI: 10.1038/s41420-022-00840-w
|View full text |Cite
|
Sign up to set email alerts
|

Bdh1 overexpression ameliorates hepatic injury by activation of Nrf2 in a MAFLD mouse model

Abstract: In 2020, a group of experts officially suggested metabolic dysfunction associated with fatty liver disease “MAFLD” as a more appropriate overarching term than NAFLD, indicating the key role of metabolism in fatty liver disease. Bdh1, as the rate-limiting enzyme of ketone metabolism, acts as an important metabolic regulator in liver. However, the role of Bdh1 in MAFLD is unclear. In this study, we used the transgenic db/db mice as a MAFLD mouse model and observed the downregulated expression of Bdh1 in fatty li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…39 Xu et al found that the overexpression of Bdh1 could attenuate high-fat diet-induced liver damage by inhibiting oxidative stress and apoptosis. 40 Our results showed that Bdh1 overexpression reduced oxidative stress and inflammatory responses in macrophages and that AAV-mediated Bdh1 overexpression reduced vascular inflammatory responses. It has been hypothesized that Bdh1 exerts a protective effect against diabetes and AS by inhibiting oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…39 Xu et al found that the overexpression of Bdh1 could attenuate high-fat diet-induced liver damage by inhibiting oxidative stress and apoptosis. 40 Our results showed that Bdh1 overexpression reduced oxidative stress and inflammatory responses in macrophages and that AAV-mediated Bdh1 overexpression reduced vascular inflammatory responses. It has been hypothesized that Bdh1 exerts a protective effect against diabetes and AS by inhibiting oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…In support of this concept, Xu et al demonstrated that the increase in NASH characteristics upon Bdh1 knockdown is associated with increased ROS levels (Xu et al, 2022). Conversely, Bdh1 overexpression successfully attenuated lipotoxicity, oxidative stress-induced hepatic injury, inflammation and apoptosis in the fatty liver from db/db mice (Xu et al, 2022). Additionally, several lines of evidence support the concept that hepatic ketogenesis might regulate NASH phenotype through mitochondrial metabolism and inflammation.…”
Section: Do Ketogenic Insufficiency Promote Non-alcoholic Steatohepat...mentioning
confidence: 98%
“…Elevated ROS causes hepatocellular damage by inducing DNA damage and increasing the accumulation of toxic lipids and proteins (Rolo et al, 2012;Masarone et al, 2018). In support of this concept, Xu et al demonstrated that the increase in NASH characteristics upon Bdh1 knockdown is associated with increased ROS levels (Xu et al, 2022). Conversely, Bdh1 overexpression successfully attenuated lipotoxicity, oxidative stress-induced hepatic injury, inflammation and apoptosis in the fatty liver from db/db mice (Xu et al, 2022).…”
Section: Do Ketogenic Insufficiency Promote Non-alcoholic Steatohepat...mentioning
confidence: 98%
“… 54 Moreover, Bdh1 overexpression ameliorates hepatic injury in a metabolic-associated fatty liver disorder (MAFLD) mouse model. 55 These findings point to SparseGMM-identified hepatic differentiation and metabolism genes as potential bona fide transcriptional biomarkers of hepatic differentiation and metabolism in healthy livers.…”
Section: Resultsmentioning
confidence: 88%